Inside Cover: In‐vivo hemodynamic imaging of acute prenatal ethanol exposure in fetal brain by photoacoustic tomography (J. Biophotonics 5/2020). Issue 5 (26th April 2020) - Shan, Tianqi; Zhao, Yuan; Jiang, Shixie; Jiang, Huabei
Abstract: The figure shows the detailed morphology of vasculature and dynamic changes of the blood vessel diameter and density and the oxygen saturation in the blood vessels in fetal brain after acute prenatal ethanol exposure in the second‐trimester equivalent murine model obtained using a real‐time photoacoustic tomography (PAT) system. Further details can be found in the article by Tianqi Shan, Yuan Zhao, Shixie Jiang, Huabei Jiang (e201960161 ). Abstract : The figure shows the detailed morphology of vasculature and dynamic changes of the blood vessel diameter and density and the oxygen saturation in the blood vessels in fetal brain after acute prenatal ethanol exposure in the second‐trimester equivalent murine model obtained using a real‐time photoacoustic tomography (PAT) system. Further details can be found in the article by Tianqi Shan, Yuan Zhao, Shixie Jiang, Huabei Jiang (e201960161 ).